2007
DOI: 10.1021/bi7002235
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the UvrABC Nucleotide Excision Repair Proteins Analyzed by Fluorescence Resonance Energy Transfer

Abstract: UvrB plays a key role in bacterial nucleotide excision repair. It is the ultimate damage-binding protein that interacts with both UvrA and UvrC. The oligomeric state of UvrB and the UvrAB complex have been subject of debate for a long time. Using fluorescence resonance energy transfer (FRET) between GFP and YFP fused to the C-terminal end of Escherichia coli UvrB, we unambiguously show that in solution two UvrB subunits bind to UvrA, most likely as part of a UvrA2B2 complex. This complex is most stable when bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
32
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 29 publications
4
32
0
Order By: Relevance
“…1a), and imaged using the same protocol as for UvrA. Because current models propose that NER is initiated by a stable complex of UvrA and UvrB3458910, and our data showed that UvrB is present at a similar level to UvrA (both ∼85 copies per cell; Fig. 3a and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…1a), and imaged using the same protocol as for UvrA. Because current models propose that NER is initiated by a stable complex of UvrA and UvrB3458910, and our data showed that UvrB is present at a similar level to UvrA (both ∼85 copies per cell; Fig. 3a and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 54%
“…The observations that UvrA and UvrB are rarely complexed in solution in vivo , and that UvrA dimers can locate damage sites independently of UvrB, suggest that the current models, in which a stable UvrA–UvrB complex scans the genome to initiate NER34578910, need revision. We propose that NER initiation is a two-step process, where UvrA performs initial damage recognition and verification, and recruits UvrB from solution to perform further damage verification.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, an UvrA•B heteromeric complex scans the DNA searching for damaged sites. The identity of the UvrA•B oligomeric state and of the searching complex have long been the subject of debate and controversy; however, two independent studies using fluorescence resonance energy transfer and single-molecule imaging of quantum-dot-labelled proteins have proposed that the ATP-bound UvrA 2 •B 2 complex is the stable form that slides along the DNA until a damaged site is encountered (8,9). Once recognized by the UvrA component, the injured strand is transferred to UvrB and UvrA is released.…”
Section: Introductionmentioning
confidence: 99%
“…Nucleotide excision repair is the process by which bulky adducts and lesions are removed and repaired from DNA [11, 12]. During nucleotide excision repair (NER), a heterotetramer, UvrA 2 UvrB 2 , recognizes and binds the damaged region [11, 13, 14]. UvrD acts after incision to release the resulting 10 to 12 bp oligonucleotide and UvrB-UvrC complex from the DNA [15–18].…”
Section: Introductionmentioning
confidence: 99%